Em-power lifting : a case study of women’s weightlifting in Aotearoa : a research report submitted in partial fulfilment of the requirement for the degree of Master of International Development, Institute of Development Studies, School of People, Environment and Planning, Te Kunenga Ki Pūrehuroa – Massey University Aotearoa New Zealand - Ogilvy, Jamie R. I. (Massey University, 2022)
Through application of an Indigenous (Māori) informed theoretical framing, articulated as Mana Wāhine values, this research report explores the phenomenon of weightlifting with Indigenous (Māori) women from Aotearoa New Zealand, as a vehicle for empowerment. The research project was guided by two main research questions, firstly, what is the role of weightlifting in developing personal, relational, and collective empowerment for Aotearoa New Zealand Indigenous (Māori) women? Secondly, how does this empowerment align with strengthening the values, understood as Mana Wāhine values, of Indigenous (Māori) women? Data was collected via in-depth semi-structured interviews, nine wāhine (female) participants and one tane (male) participant. All participants were aged between 20 – 50 years old and had been participating in strength sports as an athlete or coach or both; six female and one male who were current or past Olympic weightlifters, two female strong women competitors and one power lifter. All participants were of Māori decent or coached wāhine Māori or were allies/accomplices (Whitinui, 2021) of Māori women in strength sport. Findings suggest that weightlifting and strength-based training enhanced the development of the self, increased body satisfaction thus positivity towards body image because women identifying as feeling physically, mentally, emotionally and spiritually strong and thus powerful. Their ability to set and achieve goals was enhanced and this carried over into other areas of life. While seemingly an individual sport, feelings of belonging and camaraderie indicated better relational empowerment, as well as collective empowerment due to being part of the lifting community and subscribing to a similar kaupapa. In terms of how these changes aligned with Mana Wāhine values, wāhine spoke about having a sense of authority, notions of manaakitanga and giving back to others and the kaupapa of strong wāhine. Overall, this research highlights that strength-based sport like weightlifting can be a vehicle for personal, relational, and collective empowerment with these elements lending themselves towards strengthening Mana Wāhine values. Of great importance here was the transformative implications noted for women. However, any broader transformative impacts beyond the individuals will require the ongoing challenges of predetermined ideologies i.e., stereotypes of women not being strong, or norms, rules, exclusionary practices and under resourcing, for example, which sees women’s lifting to be situated at the margins. Empowerment of the individual is all well and good, but the individual can only go so far. “Empowerment requires changes to systems, rules, and norms, which undermine large groups of people [Māori women], as well as changes at the level of the individual” (Scheyvens, 2020, p. 120).
Research report for Master of International Development.
Keywords: Māori Masters thesis; Mana wahine; Wāhine; Korikori tinana; Hauora tinana